Bàn thêm về tứ thơ trong thơ trữ tình - Phạm, Quốc Ca (Trường Đại học Đà Lạt, 2012)
Poem structure í a familiar concept in poetry but there are still some misunderstandings. The purpose of this paper is to clarify this concept and state out some main poem structure